Mental Health, Stress, and Coping Strategies Among School-Going Adolescents: A Study of Educational Settings in Navi Mumbai Under the theme -Community-Based Mental Health Interventions at Educational Institutions (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Mental health has become an important concern among adolescents, especially at educational institutions where students face academic, social, emotional, and family-related pressures. Adolescence, particularly between the ages of 10 and 19 years, is an important stage of life noted by rapid physical, emotional, psychological, and behavioural changes. During this time, teens may feel stressed, anxious, depressed, pressured by their peers, afraid of failing, lonely, bullied, or unsure about their future. These problems can affect their academic performance, relationships, emotional stability, and general well-being.The study is based on a fieldwork intervention conducted by MSW second-year students in a school in the Kukshet area of Nerul, Navi Mumbai. The study concentrates on understanding the major mental health challenges experienced by school-going adolescents and the coping strategies they adopt to deal with these issues. It analyses how school-going adolescents manage emotional stress and psychological problems through support from family members, friends, teachers, recreational activities, social media, and other personal coping methods. The data are collected through field visits and school observations. Data were collected using a structured interview schedule from a sample of 200 respondents. The collected data is analysed and presented through various tables, charts, and diagrams to understand the mental health issues and coping patterns among school-going adolescents.The study also shows that while some school-going adolescents receive positive support and guidance from their families and peers, many others suffer silently because of stigma, lack of awareness, poor communication, and scarce access to counselling services. In many cases, students are unable to openly express their emotions or seek professional help for their problems. The paper emphasises the need to strengthen mental wellness support systems within educational institutions through counselling services, awareness programmes, peer support groups, life skills education, stress management activities, and social work interventions. It also suggests that schools, parents, teachers, social workers, and local communities should work together to establish a supportive and healthy environment for school-age adolescents in Navi Mumbai.